Does exposure to pictures of nature boost attentional control in the Stroop task?. (December 2022) - Augustinova, Maria; Banovic, Ingrid; Burca, Mariana; Ferrand, Ludovic; Iodice, Pierpaolo; Junker, Carole; Kernivinen, Vincent; Parris, Benjamin A.
Abstract: Attention Restoration Theory (ART) argues that natural environments, or stimuli associated with natural environments, can restore reduced inhibitory capacity. ART has received support from studies showing that the Stroop congruency effect (incongruent – congruent trial RTs) is reduced following exposure to nature. Given that the Stroop congruency effect conflates interference (inhibition), facilitation and response contingency effects, these previous studies have not tested the central tenet of ART. Therefore, the present study was designed to a) unambiguously assess the extent to which exposure to pictures of nature (vs. control pictures) reduces Stroop interference (incongruent – color-neutral trial RTs; i.e., prima facie evidence for restored inhibition/attentional control); b) shed additional light on cognitive processes involved in this reduction. In line with past studies, pictures of nature were perceived as more restorative compared to control pictures. However, despite being appropriately powered and showing typical Stroop findings, the present study failed to provide evidence that exposure to these restorative pictures (as opposed to control pictures) actually reduces Stroop interference: Bayesian evidence against this reduction was provided in both errors and in reaction times and this conclusion was also reinforced by sequential analyses. Consequently, the present results indicate that exposing individuals to pictures of nature is not effective for replenishing inhibitory control in the Stroop task. Highlights: It still remains unclear whether inhibition per se is replenished via exposure to nature-related stimuli. The present study was designed to assess this central tenet of Attention Restoration Theory unambiguously. No evidence was found that exposure to nature-related (vs. control) pictures actually reduces Stroop interference. Bayesian evidence against this reduction was provided in both errors and in reaction times with standard and sequential analyses. Exposing individuals to nature-related pictures is not effective for replenishing inhibitory control in the Stroop task.